RETRACTED: Quercetin Inhibits Tumorigenesis of Colorectal Cancer Through Downregulation of hsa_circ_0006990 - Chen, Bin; Wu, Linguangjin; Tang, Xiaoxia; Wang, Ting; Wang, Shuyun; Yu, Hongjie; Wan, Guangsheng; Xie, Manli; Zhang, Ruijuan; Xiao, Haijuan; Deng, Wanli (Frontiers in Pharmacology, 2022)
Quercetin can significantly inhibit the progression of colorectal cancer (CRC). However, its specific mechanism remains largely unclear. In this study, we aimed to explore the correlation among quercetin, tumour-associated macrophages (TAMs) and circular RNAs (circRNAs) in the progression of CRC and to present a novel strategy for the treatment of CRC. In this study, we revealed that quercetin could suppress the autophagy of M2-TAMs and induced their differentiation into M1-TAMs, by which quercetin significantly reversed the inhibition of M2-TAMS on CRC cell apoptosis and the promotion of M2-TAMS on CRC cell proliferation. Moreover, quercetin could promote the expression of downregulated hsa_circ_0006990 in CRC cells co-cultured with M2-TAMs, and the overexpression of hsa_circ_0006990 significantly reversed the anti-tumour effect of quercetin on CRC. Furthermore, we found quercetin can notably suppress the progression of CRC via mediation of the hsa_circ_0006990/miR-132-3p/MUC13 axis. In conclusion, our results suggested that quercetin inhibits the tumorigenesis of CRC via inhibiting the polarisation of M2 macrophages and downregulating hsa_circ_0006990. Our study provides useful insights for those exploring new methods of treating CRC.